2013
DOI: 10.1007/s12307-013-0132-4
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling Reveals Regulation of ERK Phosphorylation by Androgen-Induced Tumor Suppressor U19/EAF2 in the Mouse Prostate

Abstract: U19/EAF2 is regulated by androgens in the prostate and capable of regulating transcriptional elongation of RNA Pol II via interaction with the ELL family proteins. Inactivation of U19/EAF2 induces tumorigenesis in multiple organs; however the mechanism of U19/EAF2 tumor suppression remains unclear. To elucidate potential mechanisms of U19/EAF2 action, we performed cDNA microarray analysis and identified 164 mRNA transcripts regulated by U19/EAF2 in the mouse ventral prostate. Bioinformatics analysis indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Eaf2 loss was previously shown to activate the ERK pathway (Su, et al 2013). RTN4 is a neurite outgrowth inhibitor (Spillmann, et al 1998) that was shown to inhibit proliferation and promote apoptosis when transfected into human hepatocellular carcinoma cells (Chen, et al 2005).…”
Section: Discussionmentioning
confidence: 96%
“…Eaf2 loss was previously shown to activate the ERK pathway (Su, et al 2013). RTN4 is a neurite outgrowth inhibitor (Spillmann, et al 1998) that was shown to inhibit proliferation and promote apoptosis when transfected into human hepatocellular carcinoma cells (Chen, et al 2005).…”
Section: Discussionmentioning
confidence: 96%
“…Inactivation of EAF2 induces tumorigenesis in several organs, including lung, liver and prostate [22]. Although its mechanism of action is unknown, studies show that EAF2 functions in controlling the growth and survival of cancer cells by negatively regulating canonical Wnt/β-catenin signaling as well as the RAS-BRAF-ERK signaling pathway [23, 24]. EAF2 also reportedly binds to and stabilizes von Hippel-Lindau protein (pVHL), a tumor suppressor involved in mediating HIF1α degradation and an inhibitor of the hypoxia pathway, which suggests it is a potential metabolic regulator [25].…”
Section: Introductionmentioning
confidence: 99%
“…Of these genes, 49 had a statistically significant tendency to co‐occur in tumor specimens with ELL2 alteration, while two were mutually exclusive (Table ). None of the identified AR response genes were identified previously as also being regulated by ELL2 or EAF2 . Interestingly, only SPDEF and TM4SF1 were identified as having a statistically significant tendency to co‐occur with EAF2 alteration in prostate cancer specimens (data not shown).…”
Section: Resultsmentioning
confidence: 86%